Association between sociodemographic factors and alcohol consumption among adults aged 18–69 years in Kazakhstan: a cross-sectional study - Marat Shoranov; Anel Ibrayeva; Mirzakarim Alchinbayev; Bakyt Ramazanova; Shynar Tanabayeva; Ildar Fakhradiyev (BMJ Open)
Objective The aim of this study is to analyse the prevalence and characteristics of alcohol consumption including the patterns of heavy episodic drinking, among the adult population of Kazakhstan (18–69 years old) and identify key socio-demographic and regional factors influencing alcohol use.Design/methods A cross-sectional, population-based study was conducted from October 2021 to May 2022. Data were collected via face-to-face interviews using the standardised WHO STEPwise approach.Setting and participants The sample included 6720 adults aged 18–69 years from all 17 regions of Kazakhstan.Results Among participants, 54.1% had ever consumed alcohol, 42.5% in the past 12 months and 23.7% in the past month. Men had higher adjusted odds of alcohol consumption in the past 30 days (adjusted OR 1.57; 95% CI: 1.37 to 1.81) and heavy episodic drinking (adjusted OR 1.80; 95% CI: 1.44 to 2.24) compared with women. Younger adults (18–24 years) had lower odds of alcohol consumption (adjusted OR 0.61; 95% CI: 0.45 to 0.83) and heavy episodic drinking (adjusted OR 0.59; 95% CI: 0.37 to 0.94). Russians and Ukrainians had significantly higher adjusted odds of alcohol consumption (adjusted OR 1.48; 95% CI: 1.11 to 1.98 and OR 1.85; 95% CI: 1.14 to 3.01, respectively). Significant regional differences were found, with higher alcohol use in the northern regions and major cities. Smoking was strongly associated with alcohol consumption (adjusted OR 3.08; 95% CI: 2.65 to 3.57) and heavy episodic drinking (adjusted OR 3.72; 95% CI: 3.05 to 4.54). Education, occupation and marital status were not significant determinants.Conclusions The findings highlight the complexity of alcohol consumption patterns in Kazakhstan and the need for targeted public health interventions tailored to gender, age, ethnicity and region.